The Effect of organizational commitment on employees' performance: A Field study on Travel Agencies Category "A" in Cairo. - Emam, Mahmoud (Finance and Business Economies Review, 2019)
The study aimed to identify the impact of the organizational commitment on the employees' performance in the Egyptian travel agencies category "A" in Cairo. To achieve the objective of the study, the researcher distributed 420 forms to a sample of employees in the Egyptian travel agencies category "A". 384 valid forms were analyzed using SPSS v.24. The study found that the organizational commitment has a significant and positive impact on the employees' performance in the Egyptian travel agencies category "A."